Wide vs. narrow tax bases under optimal investment timing - Paolo M. Panteghini (Center for Economic Studies and ifo Institute (CESifo), 2004)
This article compares an ACE system with a CBIT system in an open economy. Using a realoption approach we show that, if a firm can decide when to invest, a tradeoff is found. According to traditional wisdom, a high-income firm investing in an ACE system faces a heavier tax burden at each instant. On the other hand, it finds it optimal to invest earlier, thereby enjoying a longer stream of income. If, given the same tax burden, the latter effect is great enough, the firm will prefer the ACE system. In this article we also run a simulation which shows that preference for an ACE system is a realistic result.
Keywords: H32; H25; 330; corporate taxation; open economy; timing and real options; Körperschaftsteuer; Unternehmensbesteuerung; Steuerbemessung; Steuerliches Anrechnungsverfahren; Investition; Realoption; Betriebliche Terminplanung; Theorie